Dendritic cell expression of CD24 contributes to optimal priming of T lymphocytes in lymph nodes - Zhang, Xuejun; Yu, Chuan; Liu, Jin-Qing; Bai, Xue-Feng (Frontiers in Immunology, 2023)
CD24 is a GPI anchored cell surface glycoprotein whose function as a co-stimulatory molecule has been implicated. However, the function of CD24 on antigen presenting cells during T cell responses is not well understood. Here we show that in the CD24-deficient host, adoptively transferred CD4+ T cells undergo inefficient expansion and have accelerated cell death in lymph nodes, which results in insufficient priming of T cells. Insufficient expansion of T cells in the CD24-deficient host was not due to host anti-CD24 response by NK, T and B lymphocytes. Transgenic expression of CD24 on DC in CD24-/- mice restored T cell accumulation and survival in draining lymph nodes. Consistent with these findings, MHC II tetramer staining also revealed that an antigen-specific polyclonal T cell response was reduced in lymph nodes of CD24-/- mice. Taken together, we have revealed a novel role of CD24 on DC in optimal T cell priming in lymph nodes. These data suggest that CD24 blockade should lower unwanted T cell responses such as those in autoimmune diseases.